2021
DOI: 10.1177/10731911211034564
|View full text |Cite
|
Sign up to set email alerts
|

How Universal Is a Construct of Loneliness? Measurement Invariance of the UCLA Loneliness Scale in Indonesia, Germany, and the United States

Abstract: The UCLA Loneliness Scale (ULS-20) and its short version (ULS-8) are widely used to measure loneliness. However, the question remains whether or not previous studies using the scale to measure loneliness are measuring the construct equally across countries. The present study examined the measurement invariance (MI) of both scales in Germany, Indonesia, and the United States ( N = 2350). The one-, two-, and three-factor structure of the ULS-20 did not meet the model fit cut-off criteria in the total sample. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
1
22
0
3
Order By: Relevance
“…Finally, the study was undertaken during the initial period of the COVID-19 pandemic when strict levels of physical distancing and the transition to virtual spaces were introduced. However, despite this transition, those without a history of mental illness reported levels of loneliness comparable to those observed in pre-pandemic studies (Hudiyana et al, 2021;Wu & Yao, 2008). Although we collected data on responses to the pandemic and controlled for these in the analyses, it is possible that these social adjustments may in turn have limited people's ability to help or hinder others through interpersonal interactions even though loneliness remained relatively stable (Muldoon, 2020).…”
Section: Limitations and Future Researchmentioning
confidence: 88%
“…Finally, the study was undertaken during the initial period of the COVID-19 pandemic when strict levels of physical distancing and the transition to virtual spaces were introduced. However, despite this transition, those without a history of mental illness reported levels of loneliness comparable to those observed in pre-pandemic studies (Hudiyana et al, 2021;Wu & Yao, 2008). Although we collected data on responses to the pandemic and controlled for these in the analyses, it is possible that these social adjustments may in turn have limited people's ability to help or hinder others through interpersonal interactions even though loneliness remained relatively stable (Muldoon, 2020).…”
Section: Limitations and Future Researchmentioning
confidence: 88%
“…First, as is apparent from the limitations, an extension to longitudinal analyses of cross-country data and to non-observational data seems warranted. Moreover, further studies similar to Hudiyana et al, 2021 that investigate whether cultural differences bias loneliness measurements are important to establish a firm basis for future cross-national comparative research [ 89 ]. A critical issue for examination is the heterogeneity of the effect of gender equality on loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Users also suggested that video calls and group chat features should be incorporated into the app. This suggestion might be driven by social isolation and loneliness among people from communal cultures ( 40 ). Moreover, the mobility restriction during the pandemic amplified the social isolation because migrant workers, particularly the migrant domestic workers, were not allowed by their employers to take the day-off or asked to stay at home during their day-off ( 9 ).…”
Section: Discussionmentioning
confidence: 99%